Perlindungan Hukum terhadap Korban Penipuan Jual Beli Online pada Masa Pandemi Covid-19 Di Polrestabes Surabaya - Nur Fika Ramadhani Zulkifli (CV. Syntax Corporation Indonesia, 2021)
This study discusses the legal protection of victims of online buying and selling fraud during the Covid-19 pandemic in surabaya police. The type of research used is using empirical juridical. By using data sources obtained through the results of research, books - literature books and legislation - applicable legislation. Data analysis used in this study is qualitative data analysis by collecting data that is then processed into a report. The results of the research that can be concluded are the increasing cases of online fraud, one of the causes is the impact of the COVID-19 pandemic, this is due to government policies in tackling the pandemic. The existence of a pandemic has caused considerable losses to the community, resulting in the emergence of many layoffs and increased unemployment.